A inspiração fenomenológica na concepção de ensino-aprendizagem em Paulo Freire - Giovedi, Valter Martins (2006)
The purpose of this is to analyze the freireana teaching-learning concept, emphasizing its epistemological concepts linked to existential phenomenology. In other words, the reader will find a bibliographical research performed in the sense to search categories that will evidence all the philosophical influences Paulo Freire had in his work. I hereby denominate this teaching-learning concept of existencial-phenomenology . Therefore, this text is divided into two main chapters. The first chapter has the purpose to promote a general overview of the main epistemological chains developed in western philosophy in modern times, reaching the existencial-phenomenology , passing through empirics, rationalism, naturalism, Husserl s phenomenology and Marxism. The text has the intent to contextually show the mains ideas defended by phenomenology-existencial , showing how this philosophical chain stands face the current limitations in the epistemological chains that came before. In the second chapter, there is a systematization of the freireano thinking emphasizing first the political category and then the teaching-learning concept. We tried to demonstrate how the freireano teaching-learning concept has a dimension that goes beyond conventional concepts in regards of contemplating the dialogic investigation of the curriculum as an essential element, therefore necessary, to the teaching-learning process. After configuring the freireano teaching-learning concept in all its several dimensions (dialogic, dialogic construction of the curriculum, educator role and the relation educator-educated), I finish the work by analyzing the epistemological precepts of the freireano teaching-learning concept linked to existential phenomenology. I present into categories the intension of the conscience, the being-in-the world, with-the-world and with-the-others, the teaching-learning as knowledge act and others, are present in freireano thinking and serve as fundamentals so Freire could develop and legitimate his positions regarding his teaching-learning concept and, therefore, his liberating pedagogy